STUDI LITERATUR : IMPLEMENTASI PEMBENTUKAN NILAI- NILAI KARAKTER MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA SISWA SMA - Nur Alfiatun Nikmah; Amalia Putri Shalihat; Ripsani Hadjna Boelky; Reny Radita Putri; Sherly Meidina; Afandi (Yayasan Nusantara Hasana Berdikari, 2023)
Citizenship education is one of the pillars of character building and national identity, which means that citizenship education educates citizens to be good and intelligent citizens to face world developments in the era of competition and solve social problems of life. Citizenship education has been regulated by RI Law no. 20 of 2003 regarding character education formulates that there are 18 character values that can be found in intracurricular and extracurricular. The purpose of this study was to determine the relationship between Citizenship Education and character education in students towards student character through the efforts implemented by learning Citizenship Education. This study uses the literature study method in order to obtain objective results regarding the role of learning civics education in the formation of character education for high school students. Data were obtained from secondary data in the form of scientific articles, reference books, and national proceedings for the last 10 years. In this study, it was obtained an illustration that Citizenship Education is closely related to character education. Implementation in the formation of student character can be done in three stages by the teacher, namely planning, implementation and assessment. In addition, from habituation that instills character values found in intracurricular and extracurricular activities and the use of the internet.